ON REFERRING TO CHRISTIANITY SANCTUARIES IN TABLE MOUNTAIN (MAT-LOM) - Sampiev, Israpil M. (History, Archeology and Ethnography of the Caucasus, 2019)
The article aims to verify some of the assertions made about attributing sanctuaries of Mount Stolovaya (Myat-Loam) in Ingushetia to Christianity. The principal tasks of the study are to conduct critical analysis of some of the statements of pre-revolutionary and soviet authors, related to those shrines; to check the conformity of the said shrines to the Christian places of worship; to compare rituals of the sanctuaries with the Christian ones. Pre-revolutionary imperial and soviet authors associate sanctuaries of Mount Stolovaya in the mountainous regions of Ingushetia (Myatzetli, Myattar-Dyala, Susol-Dyala) to Christianity, describing them as churches or chapels. For this purpose, names of the shrines were often distorted and then attributed to Christian saints. Those statements, without any scientific reasoning, were most likely aimed to legitimize the Russian Empire on the Caucasus’ territory, as a former Christian space. However, the study analysis of the sanctuaries, carried out by the leading experts in places of worship (architect A. Goldstein, archeologist M.B Muzhukhoev, ethnologists V. N. Basilov, V.P. Kobychev et al.) reveals that they do not comply with the established criteria of Christian monuments; rituals of praying at the sanctuaries also show no conformity to Christianity (it was forbidden for anyone to be inside the Ingush shrines except the priest; the absence of altar; animal sacrifice; feasts and dances, etc.). The analysis of architectural, ritual and ethnographic aspects of the sanctuaries on Mount Stolovaya provides the conclusion that Myatsil, Myattar-Dyala, Susol-Dyala are pagan shrines, associated with crypts as attributes of the cult of ancestor veneration. Basing on the analysis, it has been established that Myatseli and other distinctive Ingush sanctuaries, located in Kistin community of Ingushetia, were never Christian churches or chapels; attempts at associating Christian names of St. Mary or St. Matthew to the name of Myatseli and the sacred Ingush mountain Myat-Loam are unfounded. The results of the study refute the attempts of false attribution of Ingush national places of worship to Christianity and carry not only gnoseological, but also practical relevance.